Effects of combined roasting and steam cooking on NaCl reduction and quality changes in marinated salmon flesh as compared with roasting and water bath cooking. (1st April 2023) - Lian, Fengli; Cheng, Jun-Hu; Wang, Han; Sun, Da-Wen
Abstract: In this study, combining roasting with steam cooking was proposed to reduce sodium chloride (NaCl) content during cooking operations. The NaCl reduction effects of roasting-steam cooking (RS), roasting (R), and water bath cooking (WB) on marinated salmon flesh samples with different cooking times (2, 4, 6 and 8 min) were evaluated. Results showed that the NaCl contents in the samples treated by RS and R were reduced by 22.44% and 15.59%, respectively. RS could also provide high overall acceptability without compromising the taste and flavour. FTIR analysis demonstrated that RS and R increased α-helix and β-sheet and slightly decreased β-turn in sample proteins as compared with WB, indicating that RS could achieve low denaturation and weak unfolding degree of protein structure due to protein conformation inhibited by the steam. Therefore, RS could serve as a novel method for reducing NaCl contents in cooked meat products. Highlights: Roasting-steam cooking (RS) is a novel way for reducing NaCl contents in meats. RS provided high overall acceptability without compromising taste and flavour. Salt content in meat was related to water distribution and microstructure. Microstructure and water distribution were related to protein tertiary structure.